The Rise of Pluripotent Stem Cell-Derived Glia Models of Neuroinflammation - Srishti Kala; Andrew G. Strutz; Moriah E. Katt (Neurology International)
Neuroinflammation is a blanket term that describes the body’s complex inflammatory response in the central nervous system (CNS). It encompasses a phenotype shift to a proinflammatory state, the release of cytokines, the recruitment of peripheral immune cells, and a wide variety of other processes. Neuroinflammation has been implicated in nearly every major CNS disease ranging from Alzheimer’s disease to brain cancer. Understanding and modeling neuroinflammation is critical for the identification of novel therapeutic targets in the treatment of CNS diseases. Unfortunately, the translation of findings from non-human models has left much to be desired. This review systematically discusses the role of human pluripotent stem cell (hPSC)-derived glia and supporting cells within the CNS, including astrocytes, microglia, oligodendrocyte precursor cells, pericytes, and endothelial cells, to describe the state of the field and hope for future discoveries. hPSC-derived cells offer an expanded potential to study the pathobiology of neuroinflammation and immunomodulatory cascades that impact disease progression. While much progress has been made in the development of models, there is much left to explore in the application of these models to understand the complex inflammatory response in the CNS.